PENGARUH PEMBERIAN MOTIVASI OLEH GURU PAK TERHADAP MINAT BELAJAR SISWA KELAS X SMA SWASTA HKBP 2 TARUTUNG T.P 2018/2019 - jesika tampubolon (IAKN Tarutung, 2019)
vAbstract: This Research aim to know there is do not it influence which are positive and signifikan between giftmotivate by teacher of Christian Education to enthusiasm learn the student of Class X SMA of Private sectorHKBP 2 Tarutung of Study Year 2018 / 2019, with the hypothesis there are influence which are positive andsignifikan between Gift Motivate by teacher of Christian Education To Enthusiasm Learn The Student of ClassX SMA of Private sector HKBP 2 Tarutung School Year 2018 / 2019. This research use the descriptivequantitative approach inferensial, with the population all student of class X SMA HKBP 2 Tarutung amountingto 133 people by sampel amount to 40 people. Data collected with the enquette closed as much 45 item compiledby writer pursuant to variable indicator according to expert theory. Test-Drive the enquette done to 35 studentwhich is non research responder, and have been tested the validity and reliability. Result of data analysisindicate that there are influence which are positive and signifikan between Gift Motivate by teacher of ChristianEducation To Enthusiasm Learn The Student of Class X SMA Private sector HKBP 2 Tarutung School Year2018 / 2019 with the coefficient determinasi ( r2) = 53,72% and test the signifikan influence obtained FcountFtable of equal to 42,794,10, its meaning Ho refused and Ha accepted.Keyword: Gift Motivate the, Enthusiasm Learn